Diversifikasi Produk Terhadap Nilai yang Dirasakan dan Loyalitas Konsumen pada Brand Fashion Merek Nada Puspita: Persfektif Hukum Ekonomi Syari’ah - Nia Puspita Hapsari; Suhendar Sulaiman; Liza Nora (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The qualitative research explores how product diversification in local Muslim fashion brands in Indonesia shapes customer perceived value from the perspective of Islamic economic law. Using a library study approach, relevant journals, and in-depth interviews with industry players and consumers, the findings indicate that product diversification, while meeting market share needs, is interppreted as a manifestation of product compliance with Islamic principles. The method used was to collect reference sources in the form of journal literature, reference books, and online media. The results of this study provide insight into the relationship between marketing management strategies in product diversification, and perceived value from consumers and customers, as well as compliance with Sharia Law. The local brand Nada Puspita reflects not only an elegant Muslim fashion style but also brings a strong religious nuance, and cultural aesthetic value into its product dsign. This study aims to fill this gap by analyzing in depth how product diversification, and perceived value affect the sustainability of a local premium Muslim fashion brand according to Sharia economic law. The strategy is not only oriented towards market differentiation but also on the integration of religious values, modesty, and Islamic cultural identity represented through the design, and narrative of a product. This diversification strengthens brand equity, increases perceived value, and constructs loyalty among Muslim consumers. This research can contribute to the development of Islamic marketing management studies, particularly on the practice of modest fashion branding in Indonesia.